Early stage writing application for beginners with precision evaluation (alphabet module) - Intan NurMarzliny, Mohd Akmallah (2013)
Alphabets writing is one of an early stage learning which divided into number and alphabet writing. Current existing learning application for alphabet writing commonly focused on learning method, but not for evaluation on their skills and correctness. Thus, the users does not realized their precision and stroke ordering were following the accurate steps or not. Therefore, to overcome these problems, a writing application was developed to evaluate the precision and correctness in alphabet writing by implementing mouse event handler and point-in polygon method. The module of this application focused on early stage writing learning (for alphabet module). The development process of this application used the combination of Waterfall and Rapid Application Development (RAD) in order to ensure the repetitive process in design and implementation were performed. This application built using HTML5, PHP, Java script and JSON language. The result shown that the proposed solution has a capability in identify the weakness of the user writing skill by showing user level of tracing and stroke ordering.